Comparison of alternative banking systems - Karlov, Kyrylo (2019)
The bachelor thesis is devoted to the comparative analysis of alternative banking systems. I summarise the critique of the current banking system and the arguments in favour of the free banking system. The main characteristics of the selected system are the competition on the supply side of the money market, and the absence of the central banks. The criteria for analysis are a type of money, transformation process, institutions, and systems flaws. For correct comparison, systems are divided into two groups: theoretical and practical. The comparative analysis shows that the gold standard has several advantages over cryptocurrencies, and it is selected as the best practical banking system. Among the theoretical models, Hayek’s proposal outweighs the New monetary approach.